The effect of trait mindfulness on dishonesty : examination of self-control as a mediator - Chew, Kate Kuo Min (2019)
Recent studies have explored the association between trait and state mindfulness and various unethical behaviors. Despite this, there is limited knowledge on the influence of trait mindfulness on specific unethical behaviors such as dishonesty. The present study examines the relationship between trait mindfulness and dishonesty through an adapted matrix task among a convenience sample of 164 adults aged 18 to 57 years old. Logistic regression analysis was utilized as dishonesty was measured as a dichotomous variable. The results indicate that trait mindfulness has a significant negative association with dishonesty. The role of self-control as a mediator was also tested. However, the results indicate that self-control did not significantly mediate this relationship. Future studies should examine the effect of other potential mediators such as reward sensitivity and decision making. Additionally, future research addressing limitations in the current study may provide further insight into the association between trait mindfulness and dishonesty and its underlying mechanisms.